Sistema de costo por procesos y su incidencia en la rentabilidad en la empresa Furukawa Plantaciones C.A del Ecuador, periodo 2013 - Valencia Sánchez, Rosa Mariana (2014)
This research was carried out in the Province of Santo Domingo de los Tsáchilas, Canton Santo Domingo, in the company FURUKAWA CA PLANTATION OF ECUADOR. The research phase lasted 90 days; the overall objective was to establish a costing system processes and their impact on the profitability FURUKAWA PLANTATION OF ECUADOR Canton CA Santo Domingo, 2013 period. Methods, techniques and sources of information that allowed us to know the processes of production and purchase of abaca in the company was used to achieve the specific objectives, which are discussed in the results using flow charts, tables and graphs. Flowcharts were developed and interviews on the work performed in FURUKAWA PLANTATION OF ECUADOR CA to establish processes that occur for the production costs of the plantation, as well as the costs involved in the process of buying abaca. The unit and total cost of production and purchase of abaca resulting $ 347,587.42 to produce and to buy 1,645,998.88 was obtained; showing great economic difference between the two processes. It was established that the utility company is $ 1,125,603.76. Similarly the equilibrium point which resulted in $ 1,838,965.30 was determined and deducted that values below this area the company loses money